2024
DOI: 10.1002/ecs2.4752
|View full text |Cite
|
Sign up to set email alerts
|

Data assimilation experiments inform monitoring needs for near‐term ecological forecasts in a eutrophic reservoir

Heather L. Wander,
R. Quinn Thomas,
Tadhg N. Moore
et al.

Abstract: Ecosystems around the globe are experiencing changes in both the magnitude and fluctuations of environmental conditions due to land use and climate change. In response, ecologists are increasingly using near‐term, iterative ecological forecasts to predict how ecosystems will change in the future. To date, many near‐term, iterative forecasting systems have been developed using high temporal frequency (minute to hourly resolution) data streams for assimilation. However, this approach may be cost‐prohibitive or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 100 publications
1
1
0
Order By: Relevance
“…This finding is in agreement with a previous water temperature forecast study at the same reservoir, which found high forecast skill from a persistence model deeper in the lake and higher skill from a PM at the surface (Thomas et al, 2020). Individual PMs have been shown to be successful at forecasting water temperature dynamics at the lake surface at short horizons (Thomas et al, 2020;Wander et al, 2024). As weather forecast skill degrades further into the future, there is a subsequent reduction in water temperature forecasting skill at these shallower depths at longer horizons (Carey et al, 2022b;Thomas et al, 2020).…”
Section: No One Individual Model Is Optimal For All Forecast Horizons...supporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in agreement with a previous water temperature forecast study at the same reservoir, which found high forecast skill from a persistence model deeper in the lake and higher skill from a PM at the surface (Thomas et al, 2020). Individual PMs have been shown to be successful at forecasting water temperature dynamics at the lake surface at short horizons (Thomas et al, 2020;Wander et al, 2024). As weather forecast skill degrades further into the future, there is a subsequent reduction in water temperature forecasting skill at these shallower depths at longer horizons (Carey et al, 2022b;Thomas et al, 2020).…”
Section: No One Individual Model Is Optimal For All Forecast Horizons...supporting
confidence: 91%
“…However, the skill of these models is often limited by the skill of other forecasts (e.g., weather and inflow discharge) needed as model driver data (Mercado-Bettín et al, 2021;Thomas et al, 2020). Moreover, PMs also often demonstrate substantial differences in skill among forecasted sites (Thomas et al, 2023) and depths (Thomas et al, 2020), as well as at different times of year (e.g., in thermally stratified vs. mixed conditions; Thomas et al, 2020;Wander et al, 2024).…”
Section: Introductionmentioning
confidence: 99%